Identification of AF4/FMR2 family, member 3 (AFF3) as a novel rheumatoid arthritis susceptibility locus and confirmation of two further pan-autoimmune susceptibility genes. - Barton, A; Eyre, S; Ke, X; Hinks, A; Bowes, J; Flynn, E; Martin, P; Wilson, A; Morgan, A; Emery, P; Steer, S; Hocking, L; et al. (2009)
The concept of susceptibility genes common to different autoimmune diseases is now firmly established with previous studies demonstrating overlap of loci conferring susceptibility to type 1 diabetes (T1D) with both Coeliac disease and multiple sclerosis. Rheumatoid arthritis (RA) is an archetypal autoimmune disease and we, therefore, targeted putative T1D susceptibility loci for genotyping in UK RA cases and unrelated controls. A novel RA susceptibility locus at AFF3 was identified with convincing evidence for association in a combined sample cohort of 6819 RA cases and 12 650 controls [OR 1.12 95% confidence intervals (CI) 1.07-1.17, P = 2.8 x 10(-7)]. Association of two previously described loci (CTLA-4 and 4q27) with RA was also replicated (OR 0.87, 95% CI 0.82-0.94, P = 1.1 x 10(-4) and OR 0.86, 95% CI 0.79-0.94, P = 5.4 x 10(-4), respectively). These findings take the number of established RA susceptibility loci to 13, only one of which has not been associated with other autoimmune diseases.